2010
DOI: 10.1007/s12630-010-9420-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and general anesthesia

Abstract: Purpose The mechanisms through which general anesthetics cause reversible loss of consciousness are characterized poorly. In this review, we examine the evidence that anesthetic-induced loss of consciousness may be caused by actions on the neuronal pathways that produce natural sleep. Principal findings It is clear that many general anesthetics produce effects in the brain (detected on electroencephalogram recordings) that are similar to those seen during non-rapid eye movement non-(REM) sleep. Gamma aminobuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 81 publications
1
69
0
2
Order By: Relevance
“…A reduction in the coherence and information transfer among select frontal, parietal, and occipital cortical regions has been found using electrophysiological techniques (Ku et al, 2011;Lee et al, 2009bLee et al, , 2013. More generally, anesthetics have been thought to target subcortical mechanisms (Brown et al, 2010;Guldenmund et al, 2013;Mhuircheartaigh et al, 2010) including the natural sleep promoting circuits (Franks and Zecharia, 2011;Zecharia and Franks, 2009), and the neocortex itself (Hentschke et al, 2005;Hudetz, 2006;Seth et al, 2005;Velly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the coherence and information transfer among select frontal, parietal, and occipital cortical regions has been found using electrophysiological techniques (Ku et al, 2011;Lee et al, 2009bLee et al, , 2013. More generally, anesthetics have been thought to target subcortical mechanisms (Brown et al, 2010;Guldenmund et al, 2013;Mhuircheartaigh et al, 2010) including the natural sleep promoting circuits (Franks and Zecharia, 2011;Zecharia and Franks, 2009), and the neocortex itself (Hentschke et al, 2005;Hudetz, 2006;Seth et al, 2005;Velly et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…30 Decreased REM has also been described under anesthesia. 31,32 Thus, the decreased REM sleep percentage on the first night after AT is perhaps evidence of the prolonged effect of anesthetics following surgery compounded by postsurgical stress. Our study also showed decreased periodic limb movement in sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Arousal after cessation of general anesthesia provides an experimental model to investigate the neural mechanism that controls consciousness (3)(4)(5)(6), as yearly more than 312 million patients are placed under general anesthesia worldwide (7). Although the exact mechanism underlying arousal from anesthesia is unknown, ample evidence suggests a remarkable similarity between anesthesia-induced unconsciousness and deep sleep (1,3,4,6,8). The hypothalamus is a key brain region for regulation of sleep and wakefulness (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%